Potensi Bakteri Asal Bambu dalam Memproduksi Asam Indol Asetat (IAA) - Al Banna, Maisya Zahra; Arifuddin, Widiastini (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Bamboo are known having a high adaptive ability to tolerate environmental changes or stresses. Endogenous microorganisms in several parts of bamboo have been reported used as organic fertilizer and biocompost. However, bacterial potential as auxin (IAA) producer has not been widely report, especially for Torajas’ local bamboo. In this study, rhizosphere and endophytic bacteria were isolated from six different bamboo. Bamboo samples were obtained from the bamboo forest station area of North Toraja. Rhizosphere bacterial isolates were obtained from the area around the roots of bamboo plants, while endophytic bacterial isolates were obtained from roots and shoots bamboo tissue. Six rhizosphere isolates and 12 endophytic isolates were obtaind. All isolates were indentified for morphological, physiological, biochemical tests and IAA’s activities. There are 12 IAA-producing isolates, which where dominated by endophytic bacterial isolates. Based on 16S molecular identification, it was found that K12 isolates were similar to Bacillus cereus, with an IAA concentration value was 1.301 mg L-1. While K14 isolated has similiarities with Stenotrophomonas maltophilia with the abiliy to produce IAA was 2.737 mg L-1. The reconstruction of the phylogeny tree showed that K12 isolate had similiarity with Bacillus wedimannii, and K14 isolate was related to Stenotrophomonas sp.